Evaluating the effects of S-ketamine on postoperative delirium in elderly patients following total hip or knee arthroplasty under intraspinal anesthesia: a single-center randomized, double-blind, placebo-controlled, pragmatic study protocol - Zhu, Youzhuang; Feng, Wei; Kong, Qinghan; Sheng, Fang; Li, Zhichao; Xu, Weilong; Li, Qun; Han, Yan; Wu, Xiuyun; Jia, Changxin; Guo, Jie; Zhao, Yang (Frontiers in Aging Neuroscience, 2023)
Introduction Postoperative delirium (POD) is an acute, transient brain disorder associated with decreased postoperative quality of life, dementia, neurocognitive changes, and mortality. A small number of trials have explored the role of S-ketamine in the treatment of POD due to its neuroprotective effects. Surprisingly, these trials have failed to yield supportive results. However, heterogeneity in delirium assessment methodologies, sample sizes, and outcome settings as well as deficiencies in S-ketamine use methods make the evidence provided by these studies less persuasive. Given the severe impact of POD on the health of elderly patients and the potential for S-ketamine to prevent it, we believe that designing a large sample size, and rigorous randomized controlled trial for further evaluation is necessary. Methods This is a single-center, randomized, double-blind, placebo-controlled, pragmatic study. Subjects undergoing total hip or knee arthroplasty will be randomized in a 1:1 ratio to intervention (n = 186) and placebo (n = 186) groups. This trial aims to explore the potential role of S-ketamine in the prevention of POD. Its primary outcome is the incidence of POD within 3 postoperative days. Secondary outcomes include the number of POD episodes, the onset and duration of POD, the severity and subtype of POD, pain scores and opioid consumption, sleep quality, clinical outcomes, and safety outcomes. Discussion To our knowledge, this is the first pragmatic study that proposes to use S-ketamine to prevent POD. We reviewed a large body of literature to identify potential preoperative confounding variables that may bias associations between the intervention and primary outcome. We will use advanced statistical methods to correct potential confounding variables, improving the test’s power and external validity of test results. Of note, the patient population included in this trial will undergo intraspinal anesthesia. Although large, multicenter, randomized controlled studies have found no considerable difference in the effects of regional and general anesthesia on POD, patients receiving intraspinal anesthesia have less exposure to at-risk drugs, such as sevoflurane, propofol, and benzodiazepines, than patients receiving general anesthesia. At-risk drugs have been shown to negatively interfere with the neuroprotective effects of S-ketamine, which may be the reason for the failure of a large number of previous studies. There is currently a lack of randomized controlled studies evaluating S-ketamine for POD prevention, and our trial helps to fill a gap in this area. Trial registration: http://www.chictr.org.cn, identifier ChiCTR2300075796.